MODERN APPROACHES TO TEACHING FOREIGN LANGUAGES - Salimova Kamola Makhamatovna (Bright Mind Publishing, 2025)
The article discusses modern approaches to foreign language teaching that have emerged within the framework of the communicative approach (Lexical Approach, Task-Based Learning, Language Awareness, Content-Based Instruction, Dogme, Demand High). The principles underlying each approach are listed, and the corresponding lesson structure is described. Common features inherent in these approaches are identified, and parallels are drawn with current trends in domestic methods of foreign language teaching. Based on the analysis, conclusions are made about the main focuses of contemporary English-language foreign language teaching methodology.
Keywords: Approach, methodological principles, awareness, general academic skills, eclecticism.